Adolescents’ Norms of Self-Presentation on Snapchat: Bitmojis as an Expression of Identity Development - Jessica Kühn; Claudia Riesmeyer (Social Media + Society)
Adolescents’ self-presentation on social media as an expression of identity development is influenced by personal norms and perceived social norms of relevant others. Snapchat is popular and widely used by adolescents to express themselves. A Bitmoji, as an alternative to a traditional profile picture, offers a wide range of self-presentation options through an avatar editor, including body stature and pose, individual facial features, and (branded) clothing. Based on 53 in-depth interviews with adolescents between the ages of 11 and 16, we investigated how Bitmojis are used for self-presentation and where the underlying action-guiding norms come from. Our study revealed the high perceived relevance of Bitmojis among adolescents who consciously use their Snapchat avatar to express themselves. True self-behavior is essential for some adolescents, evidenced by single, regular, or daily changes to Bitmojis’ hairstyles and clothing. Others engage in false self-behavior, displaying an ideal self to hide disliked body features or showing a false self to experiment with their digital identity. The perceived social norms of the peer group play an important role for adolescents as their personal norms.